Sustainable E-Commerce Adoption : Green Supply Chain Practices and Consumer Perceptions - Bhatta, Shreepathy Ranga; Shetty, Dasharathraj K.; Shenoy, Sandeep S.; Rodrigues, Lewlyn L. R.; Ola, Md Obaidul (Prabandhan: Indian Journal of Management, 2026)
Purpose : The study examined the dynamics of e-commerce customers’ perceptions about green supply chain (GSC) practices and how these result in platform usage in the Indian context. The empirical research explored the combined influence of technology acceptance factors and GSC practices on perceived sustainability and usage behavior. Design/Methodology/Approach : Based on the literature, a conceptual framework was developed to propose the hypothesized relations between the adopted constructs. A systematically validated questionnaire was used to collect 416 useful responses from e-commerce users. The analysis and tests were done using partial least squares structural equation modeling to make meaningful inferences. Findings : It was found that green logistics, green packaging, and design had a positive influence on perceived environmental sustainability. However, most green practices did not directly influence behavioral intention to use e-commerce. Performance expectancy strongly influenced behavioral intention to use platforms. The research also pointed to a “usage-perception” gap, meaning that there was no enhancement in sustainability perception with continued platform use in the absence of observable feedback messages. Hedonic motivations had a marginal influence on behavioral intention. Practical Implications : The findings suggested that e-commerce platforms may strengthen consumer sustainability awareness by incorporating visible sustainability cues, such as eco-labels, carbon tracking, or sustainability dashboards, during the shopping experience. Originality/Value : This research introduced the concept of a “usage-perception gap,” which means that repeated platform use does not necessarily strengthen awareness of sustainability among users until visible sustainability signals are presented to customers to shape their positive perceptions.